A Study of the Usage of Artificial Intelligence in Scientific Research and Education - Peng Ruisen (ITM Web of Conferences)
Nowadays, the speed of spearing of artificial intelligence is getting faster. Likely commercialization can make people’s lives more convenient, if scientific research gets help from artificial intelligence, the efficiency of scientific research will significantly increase. Tliis paper shows a general situation of the usage of artificial intelligence hi scientific research and education. By combining the essential information from recent papers about tliis field, this paper analyses the crucial problem scientists face and the general solving method. Ilie mam problems are the randomness and the nature of Blackbox, and the general solving method is to add a part of the model to let the model “understand” the principles and theorems that are in the field. Also, the paper generates a general situation of the usage of artificial intelligence hi education, which is speaking out at an increasing speed. The paper is a conclusion of the situation that the character of artificial intelligence hi scientific research and education. Tliis paper expects to offer a clear cognition and deep understanding about this field.